Public Perception About Climate Change in GilgitBaltistan (Pakistan) (Journal of Asian Development Studies, 2023)
Geospatial positioning of Gilgit-Baltistan exposed the land of the mighty Himalaya-HindukushKarakoram region to adverse impacts of climate change. Climate change is a "Global" issue thatcalls for "Glocal" action. Deficit and impaired public perceptions of climate change and itsimposed risks and adverse impacts could herald climate change adaptation, mitigation, andresilience policies as well as practices at the local level. Climate Change can be evident overdecades, and it is often challenging to perceive it in the short run by personal experiences.Adequate public perception and beliefs regarding climate change pave the way for efficient climatechange actions. The study explored the role of demographic and socio-economic factors, i.e. age,gender, employment status, education level, and access to information and warning systems, inshaping climate change public perception in mountain communities of Gilgit Baltistan (GB).Survey data were collected using random stratified sampling across the GB overall 892observations were collected. The Logistic regression analysis results reveal that access to warningsystems through mobile phones, formal education, employment, adult people, and malerespondents tend to have higher levels of climate change perception and beliefs. The study alsofound that most respondents have experienced an increase in temperature and a change inprecipitation patterns, with increased hazardous incidences such as floods, avalanches, andlandslides. The research findings recommend developing an integrated policy framework for localclimate actions by strengthening education, disseminating warning systems, and promotingemployment opportunities for inclusive climate change adaptation and mitigation practices in theGB.